KONSEPSI SISTEM PENDIDIKAN ISLAM DALAM PERSPEKTIF HASAN LANGGULUNG - Hatmiah Hatmiah (Cross-border, 2021)
When the Islamic education tries to offer an integrated educational system to fulfill the blank space of general material and Islamic material, this policy will become as if a load for learners. Then, there is a need an effort to do a modernisation of Islamic education system. So, the concept of Islamic educational system from the perspective of Hasan Langgulung is very relevant and needed in education of this era. This is a library research with using hermeneutic approach. The basics of Islamic education are the Holy Koran and the Hadith. The function is to develop the potential (nature) which exist in human beings. Furthermore, the aim of Islamic education is to make human beings become Abdullah and Khalifatullah. Revealed knowledge, social and natural sciences must exist in curriculum of Islamic education. In addition, the content should also be integrated to the learners have integrated personality and observation of reality. There is no dualism of knowledge. Furtermore, aspect spritual, psychological and social also must exist in the curriculum content. At the middle school used "Interdisciplinary Approach" while in elementary school used "Basic Skills". In doing evaluation, they have to emphasize the aspect of wisdom and nobility (virtues) in addition to aspects of selecting and affirmation (reward). Furthermore, the roles of teachers in Islamic education are as a transmitter, a motivator and a facilitator. Educational funding is a shared responsibility. It also incorporates decentralization and centralization sytems. There are some principles in the administration of Islam, among others emphasize faith and morals in the works; justice and equality; discussion; division of labor and tasks; adhering to the planning, organization, supervision, monitoring and follow-up; awards, good relationships and good relations with employees; emphasizes the ability, experience and sincerity in the nomination, appointment, promotion and enhancement of the mandate in the work.